Development of Sasirangan Liquid Waste Treatment System Using Ozonization Method Using Composite Ceramic Filter Media Based on Water Chestnut (Eleocharis Dulcis) - Khalis, Raida Salsabila; Margareta, Margareta; Hasbullah, Hasbullah; Suarso, Eka; Fitriana, Syifa; Farisa, Ulya (Journal of Physics and Its Applications, 2023)
Sasirangan Liquid Waste (SLW) contains heavy metals and chemicals with BOD and COD concentrations exceeding the waste water quality standards in accordance with the Minister of Environment and Forestry Regulation Number P.16 of 2019. The aim of this research is to design and develop a SLW processing system using filter media and composite ceramics made from water chestnut (Eleocharis dulcis). Based on previous research, using the filtration method; filtration and adsorption; filtration, adsorption, sedimentation and ozonization. Filtration method can remove solid particles and sediment from water, so the water appears clearer. The water purification process that involves a filtration method using slow sand filter (SSF), which additional processes are needed either before or after the SSF is carried out. Meanwhile, the use of water chestnut has been carried out by several researchers due to its high active carbon content, namely 50.68%. In this research, we combine several methods including filtration, sedimentation, and ozonization. Water chestnut has a bound carbon content of 84.53% after being activated with an H2SO4 activator, where the largest porosity is found in ceramics with activated charcoal composite materials with variations of the H2SO4 activator. Apart from that, chestnut also has a cellulose content of 35.32% so it has the potential to be effective as a ceramic composite material in sasirangan liquid waste processing filters, especially as an adsorbent. The benefits obtained from the results of this research can be a scientific reference for the use of water chestnut as a filter media and composite ceramic.